Induction of complex immune responses and strong protection against retrovirus challenge by adenovirus-based immunization depends on the order of vaccine delivery. Issue 1 (December 2017) - Kaulfuß, Meike; Wensing, Ina; Windmann, Sonja; Hrycak, Camilla; Bayer, Wibke
Abstract Background In the Friend retrovirus mouse model we developed potent adenovirus-based vaccines that were designed to induce either strong Friend virus GagL85–93 -specific CD8+ T cell or antibody responses, respectively. To optimize the immunization outcome we evaluated vaccination strategies using combinations of these vaccines. Results While the vaccines on their own confer strong protection from a subsequent Friend virus challenge, the simple combination of the vaccines for the establishment of an optimized immunization protocol did not result in a further improvement of vaccine effectivity. We demonstrate that the co-immunization with GagL85–93 /leader-gag encoding vectors together with envelope-encoding vectors abrogates the induction of GagL85–93 -specific CD8+ T cells, and in successive immunization protocols the immunization with the GagL85–93 /leader-gag encoding vector had to precede the immunization with an envelope encoding vector for the efficient induction of GagL85–93 -specific CD8+ T cells. Importantly, the antibody response to envelope was in fact enhanced when the mice were adenovirus-experienced from a prior immunization, highlighting the expedience of this approach. Conclusions To circumvent the immunosuppressive effect of envelope on immune responses to simultaneously or subsequently administered immunogens, we developed a two immunizations-based vaccination protocol that induces strong immune responses and confers robust protection of highly Friend virus-susceptible mice from a lethal Friend virus challenge.